Research on Anchor Cable and C-Shaped Tube Support Method in Deep Layers Roadway, Experimental Study, and Numerical Simulation - Renliang Shan; Shupeng Zhang; Shengchao Xiao; Junqi Liang (Shock and Vibration)
In roadways with high ground stress or burial depths, the joints distributed within rock formations are subject to complex stresses and interlayer misalignments frequently. Rock bolts and cable bolts anchored in the rock formations are subject to tensile and shear forces. Most of the bolts used in roadway engineering are local anchored, resulting in insufficient shear strength at the bolt free end close to roadway surface and increasing bolts breaking. The anchor cable and C-shaped tube (ACC) is a highly prestressed cable bolt that can withstand high shear force in its free end. This paper examines the effect of the relationship between C-shaped tube length and joint location on the shear resistance of ACC by double shear tests. To fully exploit the ACC’s shear resistance, the C-shaped tube ends should be at least 30 cm beyond the joint. The effect of preload and concrete spray thicknesses on roadway deformation and plastic zone is investigated by numerical simulation. Results show that ACC and concrete spraying layer can form a stable extruded arch structure, so that the broken and soft rock within the loosen zone is in three-dimensional-stress state, effectively improving surrounding rock properties and controlling its deformation size. Based on these results, the ACC support design method is proposed.